EFEKTIVITAS METODE DISKUSI DALAM PENGEMBANGAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PAI DI SMAN 2 KOTA BEKASI - ., Munawaroh; Loeis, Wisnawati (Turats, 2016)
The purpose of this study is to investigate the implementation and effectiveness of the method of discussion at SMAN 2 Bekasi. Implementation of the discussions at SMAN 2 Kota Bekasi learning process to involve students actively using discussion, teachers form students in the class into 6-7 groups, then teachers present learning materials and provide opportunities for students to conduct scientific debate, then students begin exchange opinions, ask and answer questions based on the knowledge and experience gained, so that the results of these discussions could solve the problem and increase the knowledge of students. Discussion method has not been effective to develop students' critical thinking skills. It can be seen only partially active students explain, ask questions, answer questions, exchange ideas and work together to solve a problem. While most of the other students are still embarrassed or do not dare to answer and ask questions. Factors supporting the implementation of which is teacherled discussions and their supporting infrastructure. And obstacles/barriers facing: first, the difficulty to encourage all students to actively argue, ask questions and seek information. Second, the discussion in a widespread discussion that requires a considerably long time. Therefore, teachers and students should be able to set the course of discussions in line with the time/hours of lessons available.